UNIT 5.26 Use of the SHuffle Strains in Production of Proteins. (1st August 2016) - Ren, Guoping; Ke, Na; Berkmen, Mehmet
Abstract : Escherichia coli continues to be a popular expression host for the production of proteins, yet successful recombinant expression of active proteins to high yields remains a trial and error process. This is mainly due to decoupling of the folding factors of a protein from its native host, when expressed recombinantly in E. coli . Failure to fold could be due to many reasons but is often due to lack of post‐translational modifications that are absent in E. coli . One such post‐translational modification is the formation of disulfide bonds, a common feature of secreted proteins. The genetically engineered SHuffle cells offer an expression solution to proteins that require disulfide bonds for their folding and activity. The purpose of this protocol unit is to familiarize the researcher with the biology of SHuffle cells and guide the experimental design in order to optimize and increase the chances of successful expression of their desired protein of choice. Example of the expression and purification of a model disulfide‐bonded protein DsbC is described in detail. © 2016 by John Wiley & Sons, Inc.